Composite film structures containg ZnS, CdS nanoparticles prepared by MOC pyrolysis at low temperatures - Svechnikov, G.S.; Zavyalova, L.V.; Roshchina, N.N.; Prokopenko, I.V.; Berezhinsky, L.I.; Khomchenko, V.S.; Litvin, O.S. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2004)
New composite structures containing ZnS, CdS nanoparticles were prepared with bright light-blue colour of a luminescence. The structures were formed by spraying organic solution of zinc or cadmium ditiocarbamate onto substrates at temperatures within the range 40…120°C. It was established that the film emission maximum monotonously shifts into short-wave spectral region at the decreasing substrate temperature: from 590 nm (Ts = 120°C) to 500 nm (Ts = 50°C) for ZnS and from 510 nm (Ts = 120°C) to 450 nm (Ts = 40°C) for CdS. This fact can be explained by the quantum size effect: X-ray analysis has shown that researched films contain crystalline particles of 1…5 nm size.